Diagnóstico dos resíduos sólidos de construção civil e demolição da cidade de Tangará da Serra - MT - Diniz Neto, Ronaldo Pereira (2018)
Civil construction has always been prominent in the world economy. It would not be different in Brazil. This is due to the number of jobs generated, the volume and variety of materials used in the works and, above all, the impacts caused to the environment in general. These impacts are largely due to the mismanagement of natural and / or industrialized resources, in the acquisition, storage and application processes, in the different stages of the buildings. Leftovers or waste generate volumes which, if left unmanaged, are generally deposited in the vicinity of the undertaking, causing disruption to the local community. These disorders, in turn, exposes another problem, the lack of municipal management with construction and demolition waste, the so-called RCD. This work proposes to collect the amounts of RCD generated in the municipality of Tangará da Serra-MT, through data collected from the municipal management bodies and companies in the field of waste collection, calculate the total annual volumes of generation, identify the authorized areas or irregular waste disposal and, finally, to present a basic roadmap for a methodological proposal for the Integrated Management of Construction and Demolition Waste. In order to achieve these objectives, three constructions of different standards were studied, calculating the rate of waste generation per square meter and applying the said rate to the total area licensed by the municipality, in the period of one year, in the years 2016 and 2017. It was also the quantity of rubble carried to the municipal landfill, as well as the quantity collected from the buildings in the urban perimeter, informed by the collection companies. In the analysis of the results, a considerable volume of RCD is observed, in the order of: 16.81 tons / day, data obtained from the sanitation agency; 19.28 ton / day, obtained through the licensed areas method; 112.80 ton / day, obtained by the collection companies. 9 areas of RCD discarding were still diagnosed in the city, being considered 2 stable and 7 active. Of the 9 areas, 2 are public, 3 are private, with no licensing for operation, therefore irregular and 4 being public highway margins. In this way, the work presents the diagnosis and a road map for the Integrated Management of the RCD, presented in the form of a flow chart, with actions for the Municipal Management Program of the RCD, focused on public management and the RCD Management Project, mainly directed to large generators, having as final products: Waste for paving, Reuse in construction; Recyclable and non-usable waste.